Countering Node Misbehavior Attacks using Trust Based Secure Routing Protocol - Adnan Ahmed; Kamalrulnizam Abu Bakar; Muhammad Ibrahim Channa; Khalid Haseeb (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
Wireless sensor networks have gained remarkable appreciation over the last few years. Despite significant advantages and tremendous applications, WSN is vulnerable to variety of attacks. Due to resource constraint nature of WSN, applicability of traditional security solutions is debatable. Although cryptography, authentication and confidentiality measures help in preventing specific types of attacks but they cannot safeguard against node misbehavior attacks and come at significant cost. To address this problem, we propose a Trust Based Secure Routing Protocol (TBSRP) which adopts on-demand routing principle and relies on distributed trust model for the detection and isolation of misbehaving nodes. The TBSRP aims to establish shortest path that contain all trusted nodes, identify packet forwarding misbehavior caused by malicious and faulty nodes and reroute the traffic to other reliable paths. The performance of TBSRP is evaluated in terms of packet delivery ratio, average end-to-end delay, normalized routing load and average throughput. Simulations results show that TBSRP can achieve both high delivery ratio and throughput in presence of various numbers of misbehaving and faulty nodes.